Simultaneous spectrophotometric estimation of rabeprazole sodium and itopride hydrochloride in capsule formulations - Heralgi, R V; Simpi, C C; Kalyane, N V; Karajgi, S R (Asian Journal of Pharmaceutics (AJP), 2014)
A simple, precise, and economical procedure for the simultaneous estimation of rabeprazole sodium and itopride hydrochloride in tablet formulation has been developed. Rabeprazole sodium belongs to the class of proton pump inhibitor and Itopride hydrochloride belongs to the class of anticholinesterase activity as well as dopamine D2 receptor antagonistic activity, is being used for the symptomatic treatment of various gastrointestinal motility disorders. The present method involves the solving of simultaneous equations (Vierodt’s method). Rabeprazole sodium has absorbance maxima at 283 nm in phosphate buffer (pH 7.4) and itopride hydrochloride absorbance maxima at 258 nm in phosphate buffer (pH 7.4). Both these drugs obey Beer’s law in the concentration range employed for the present method. The result of analysis has been validated statistically by recovery studies.The slope and intercept for rabeprazole sodium were 0.0407 and 0.02 and for itopride hydrochloride were 0.0214 and 0.168, respectively, as determined by the method of least squares. The results were found satisfactory and reproducible.The method was applied successfully for the estimation of rabeprazole sodium and itopride hydrochloride simultaneously in tablet dosage to form without the interference of common excipients.